Hydrochemical study at Águas de Santa Bárbara Spa, São Paulo State, Brazil - Bonotto, Daniel Marcos [UNESP] (2020)
The thermal and mineral waters use in Brazil is not recent due to arrival of European immigrants, mainly from Portugal. The construction of thermal and non-thermal spas for therapeutic and leisure purposes reached a maximum number in the 1930s and 1950s, mainly at São Paulo (SP) and Minas Gerais (MG) states. The Brazilian Code of Mineral Waters (BCMW) was established in this time, under French influence, by Register 7841 published on 8 August 1945. It classifies the mineral waters for spas and bottling uses, as well the potable waters for bottling, taking into account several parameters. According to temperature, the waters may be considered cold (<25°C), hypothermal (25-33°C), mesothermal (33-36°C), isothermal (36-38°C), and hyperthermal (>38°C). Other classes defined by the BCMW are: radiferous, radioactive, thoriferous, carbogaseous, bicarbonate-alkaline, earth-alkaline, sulfated, sulfured, nitrated, chlorinated and ferruginous. Águas de Santa Bárbara spa at São Paulo State is situated in the Paraná basin, a huge sedimentary area of southern Brazil, with extensions into Paraguay, Uruguay and Argentina. Spring waters and deep tube wells have exploited groundwaters there from Bauru, Serra Geral and Botucatu formations of the Paraná sedimentary basin. Some waters have been bottled for drinking purposes, whereas other are used for bathing and health treatment in a spa constructed by the municipality of Águas de Santa Bárbara. In such case, the waters have been classified as hypothermal. This chapter reports a hydrochemical study focusing the waters in that spa, describing the analytical data obtained for major constituents, trace elements and dissolved radon with the aim of increasing the knowledge of that very important hydric resource for the municipality.